PENERAPAN PEMBELAJARAN AKTIF KREATIF EFEKTIF DAN MENYENANGKAN (PAKEM) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA KELAS IX MATA PELAJARAN FIQIH MTs GUPPI 03 BELANGGA - Ardani Muhammad Aji (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2025)
Abstract. This study uses qualitative methods to investigate things in the natural environment and try to interpret the phenomena that are happening. Qualitative research can be defined as a planned activity, covering all aspects of interpretation that make it easier for participants and informants to be seen. The research approach used in this research is a phenomenological approach which examines the application of guidance and counseling in moral development in the digital era. The subjects and objects in this study were the principal, guidance and counseling teachers, akidah akhlak teachers and students, while the BK Archives, case notes and profile documents of MAS Aisyiyah City Binjai are secondary data. In data collection, the methods used are observation, interviews and documentation. In analyzing the data the researcher used qualitative analysis with the steps of data exposure, data reduction and drawing conclusions. The instruments used in this study were interviews, observation and documentation. The results showed that (1) The moral condition of class X students towards developments in the digital era was quite good (2) The implementation of guidance and counseling carried out by BK teachers was effective by implementing various BK programs (3) Obstacles in character building for class X students of course mostly influenced by the flow of digitalization so that their behavior changes (4) Solutions to overcome the various obstacles that occur in building morals in the digital era, namely by mutual cooperation between madrasas, parents and students to always advance BK service activities.